Increased Endocannabinoid Signaling Reduces Social Motivation in Intact Rats and Does Not Affect Animals Submitted to Early-Life Seizures - Ribeiro, Fernanda Teixeira; de Serro-Azul, Marcia Ivany Silva; Lorena, Fernanda Beraldo; do Nascimento, Bruna Pascarelli Pedrico; Arnold, Alexandre José Tavolari; Barbosa, Geraldo Henrique Lemos; Ribeiro, Miriam Oliveira; Cysneiros, Roberta Monterazzo (Frontiers in Behavioral Neuroscience, 2020)
The early life status epilepticus (SE) causes high anxiety and chronic socialization abnormalities, revealed by a low preference for social novelty and deficit in social discrimination. This study investigated the involvement of the endocannabinoid system on the sociability in this model, due to its role in social motivation regulation. Male Wistar rats at postnatal day 9 were subjected to pilocarpine-induced neonatal SE and controls received saline. From P60 the groups received vehicle or JZL195 2 h before each behavioral test to increase endocannabinoids availability. In the sociability test, animals subjected to neonatal SE exhibited impaired sociability, characterized by social discrimination deficit, which was unaffected by the JZL195 treatment. In contrast, JZL195-treated control rats showed low sociability and impaired social discrimination. The negative impact of JZL195 over the sociability in control rats and the lack of effect in animals subjected to neonatal SE was confirmed in the social memory paradigm. In this paradigm, as expected for vehicle-treated control rats, the investigation toward the same social stimulus decreased with the sequential exposition and increased toward a novel stimulus. In animals subjected to neonatal SE, regardless of the treatment, as well as in JZL195-treated control rats, the investigation toward the same social stimulus was significantly reduced with no improvement toward a novel stimulus. Concerning the locomotion, the JZL195 increased it only in control rats. After behavioral tests, brain tissues of untreated animals were used for CB1 receptor quantification by Elisa and for gene expression by RT-PCR: no difference between control and experimental animals was noticed. The results reinforce the evidence that the early SE causes chronic socialization abnormalities, revealed by the low social interest for novelty and impaired social discrimination. The dual FAAH/MAGL inhibitor (JZL195) administration before the social encounter impaired the social interaction in intact rats with no effect in animals subjected to early-life seizures.